Analysis of financial position and performance of selected Indian Automobile Companies - Tata Motors and Maruti Suzuki India Limited - Raghu, Surakshith (2022)
The thesis, titled "Analysis of the financial position and performance of Tata Motors and Maruti Suzuki India Limited," analyses the balance sheet and income statements of the two Indian automobile manufacturers to ascertain their financial status and performance. The data is derived from annual reports filed by Tata Motors and Maruti Suzuki India Ltd. The data pertains to the preceding five years, from 2017 to 2021. The data was analyzed using Microsoft Excel. The analysis employs various statistical techniques, including horizontal analysis, vertical analysis, and ratio analysis. Ratio analysis incorporates liquidity ratios, leverage ratios, profitability ratios, and activity ratios. The findings of the analysis are discussed in detail under the result and discussion chapter. Tata Motors has a strong asset foundation, while Maruti Suzuki has a smaller liability base. Maruti Suzuki is performing well in profitability, liquidity, and leverage ratios. On the other side, Tata Motors has a poor track record of profitability ratios due to recorded losses over the last four years. The conclusion is based on the results and discussion chapters.